Assessing the impact of anti-microbial showerheads on the prevalence and abundance of opportunistic pathogens in shower water and shower water-associated aerosols - Pitell, Sarah; Haig, Sarah-Jane (Frontiers in Microbiomes, 2023)
Respiratory infections from drinking water-associated pathogens that can cause infections in the immunocompromised (DWPIs) are increasing, yet knowledge of DWPI aerosolization and if dynamics are DWPI-specific is lacking. Although there are several DWPI mitigation strategies, the use of antimicrobial showerheads is one of the easiest and most economical. There are many manufacturers and designs of antimicrobial showerheads that claim to remove microorganisms from shower water, yet all fail to assess efficacy in realistic conditions. In this study, a custom-built shower laboratory housing triplicates of three different showerheads (antimicrobial filter-based, antimicrobial silver-embedded and conventional acrylonitrile butadiene styrene plastic) were used to assess the physiochemical and microbial dynamics in shower water and respirable shower waterassociated aerosols (1µm -5 µm) over the course of 84 days. Collectively, findings from the study suggest that showerheads marketed as antimicrobial produce similar chemical and DWPI water quality to non-antimicrobial showerheads (p= >0.05) when operated under real-world conditions, however marked differences in the rare microbial community were present. In addition, although there were no differences in absolute DWPI abundance between showerhead type, each DWPI peaked in concentration at a different biofilm ages, suggesting that potential DWPI inhalation risk is DWPI-specific and influenced by the number of days of operation of the showerhead.